2012
DOI: 10.1080/14786419.2010.546796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Danggui Buxue Tang, a traditional Chinese herbal decoction, on high glucose-induced proliferation and expression of extracellular matrix proteins in glomerular mesangial cells

Abstract: Diabetic nephropathy (DN) is the leading cause of end-stage failure of the kidney, but the efficacy of currently available strategies for the prevention of DN remains unsatisfactory. In this study, we investigated the effects of Danggui Buxue Tang (DBT), a Chinese herbal decoction prepared from Radix Astragali (RA) and Radix Angelicae sinensis (RAS), on high glucose-induced proliferation and expression of laminin, type IV collagen (collagen IV) and fibronectin in glomerular mesangial cells (GMCs). The cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
5
11
0
Order By: Relevance
“…[8,9] Moreover, DBT inhibits increased cell proliferation and the expression of major extracellular matrix proteins, exhibiting a stronger effect than either RA and RAS alone. [10] Previous results have indicated that DBT has antihepatic fibrosis effects in rats; the optimized weight ratio of the extraction that had the best general effects was 5 : 1 for RA/RAS, which, interestingly, is in accordance with the weight ratio used in ancient preparations. [11] Our previous studies suggested that total glucosides of Danggui Buxue Tang (DBTG) have protective action against lung fibrosis in rats via a reduction of proinflammatory cytokines (tumour necrosis factor a and transforming growth factor b1) or a decrease of ECM deposition via inhibition of type I collagen expression in lung tissues.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…[8,9] Moreover, DBT inhibits increased cell proliferation and the expression of major extracellular matrix proteins, exhibiting a stronger effect than either RA and RAS alone. [10] Previous results have indicated that DBT has antihepatic fibrosis effects in rats; the optimized weight ratio of the extraction that had the best general effects was 5 : 1 for RA/RAS, which, interestingly, is in accordance with the weight ratio used in ancient preparations. [11] Our previous studies suggested that total glucosides of Danggui Buxue Tang (DBTG) have protective action against lung fibrosis in rats via a reduction of proinflammatory cytokines (tumour necrosis factor a and transforming growth factor b1) or a decrease of ECM deposition via inhibition of type I collagen expression in lung tissues.…”
Section: Introductionsupporting
confidence: 56%
“…Indeed, recent pharmacological studies indicated that DBT has the ability to promote haematopoietic function, stimulate cardiovascular circulation, prevent osteoporosis, increase antioxidation activity and stimulate the immune system [8,9] . Moreover, DBT inhibits increased cell proliferation and the expression of major extracellular matrix proteins, exhibiting a stronger effect than either RA and RAS alone [10] . Previous results have indicated that DBT has antihepatic fibrosis effects in rats; the optimized weight ratio of the extraction that had the best general effects was 5 : 1 for RA/RAS, which, interestingly, is in accordance with the weight ratio used in ancient preparations [11] .…”
Section: Introductionmentioning
confidence: 99%
“…And no significant changes were observed in the electrolytes levels, suggesting that RRF did not affect the function and equilibrium of body fluid. It is noteworthy that the levels of blood glucose and triglyceride markedly decreased in the dose groups, compared to respective controls, indicating that RRF might exert hypoglycemic and lipid-modulating activity, which in some extent corresponded with previous reports of similar pharmacological activities of DBT (Kea et al, 2012;Zhang et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…The most popular formulation is Danggui Buxue Tang (DBT) composed of Astragalus and Angelica at a 5 : 1 ratio, which is mainly used to treat anemia due to various causes via promoting hematopoiesis. 1) In recent years, studies have shown that DBT also has other pharmacological effects, such as enhancing immunity, 2) antagonizing diabetic nephropathy, 3) cardiovascular protection, 4) anti-fibrosis, 5,6) estrogen-like effect, 7,8) among others. Concerning the hematopoietic function of the AstragalusAngelica combination, most studies have revealed that Astragalus mixed with Angelica at 5 : 1 can strongly promote hematopoiesis.…”
mentioning
confidence: 99%